Day-to-day quantification of changes in global lightning activity based on Schumann resonances - Bozoki, T.; Satori, G.; Williams, E.; Guha, A.; Liu, Y.; Steinbach, P.; Leal, A.; Herein, M.; Atkinson, M.; Beggan, C. D.; DiGangi, E.; Koloskov, A.; et al. (My University, 2023)
The importance of lightning has long been recognized from the point of view of climate-related phenomena. However, the detailed investigation of lightning on global scales is currently hindered by the incomplete and spatially uneven detection efficiency of ground-based global lightning detection networks and by the restricted spatio-temporal coverage of satellite observations. We are developing different methods for investigating global lightning activity based on Schumann resonance (SR) measurements. SRs are global electromagnetic resonances of the Earth-ionosphere cavity maintained by the vertical component of lightning. Since charge separation in thunderstorms is gravity-driven, charge is typically separated vertically in thunderclouds, so every lightning flash contributes to the measured SR field. This circumstance makes SR measurements very suitable for climate-related investigations. In this study, 19 days of global lightning activity in January 2019 are analyzed based on SR intensity records from 18 SR stations and the results are compared with independent lightning observations provided by ground-based (WWLLN, GLD360, and ENTLN) and satellite-based (GLM, LIS/OTD) global lightning detection. Daily average SR intensity records from different stations exhibit strong similarity in the investigated time interval. The inferred intensity of global lightning activity varies by a factor of 2–3 on the time scale of 3–5 days which we attribute to continental-scale temperature changes related to cold air outbreaks from polar regions. While our results demonstrate that the SR phenomenon is a powerful tool to investigate global lightning, it is also clear that currently available technology limits the detailed quantitative evaluation of lightning activity on continental scales.
Keywords: Global Lightning Activity; Schumann Resonances